ANALISIS KELAYAKAN FINANSIAL USAHA PEMBUATAN TEMPE KEDELAI SKALA MIKRO DI KECAMATAN SEMARANG BARAT - TINJUNG MARY PRIHTANTI, GALIH SETO WICAKSONO, (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2019)
This study aims to analyze the feasibility of the financial business of making micro-scale tempeh in Semarang Barat Sub-district in 2018. This research is a quantitative study using a survey method with 30 respondents with criteria as experts in business tempeh agrondustry in Semarang Barat Sub-district. Investment feasibility analysis uses Net Present Value (NPV) analysis, Internal Rate of Return (IRR) and R / C Ratio analysis to find out whether there is a business tempeh agroindustry in Semarang Barat Sub-district that is feasible or not. The results of the feasibility analysis of tempe making business for 3 years, the business tempeh agroindustry is feasible to be developed, this is based on the results of research that shows the NPV (+) value of Rp. 61,730,980 which shows that the industry is feasible for investment. While the IRR (65.8%)> interest rates on commercial bank loans (DF = 11%) indicate that the business of making tempe is feasible for investment. And the value of R / C ratio (1.156)> 1, which means that the business tempeh agroindustry in Semarang Barat sub-district is feasible.Keywords : Agroindutsry, Financial feasibility, Tempeh